Metabolic decisions in development and disease—a Keystone Symposia report. Issue 1 (19th August 2021) - Cable, Jennifer; Pourquié, Olivier; Wellen, Kathryn E.; Finley, Lydia W. S.; Aulehla, Alexander; Gould, Alex P.; Teleman, Aurelio; Tu, William B.; Garrett, Wendy Sarah; Miguel‐Aliaga, Irene; Perrimon, Norbert; Hooper, Lora V.; et al.
Abstract: There is an increasing appreciation for the role of metabolism in cell signaling and cell decision making. Precise metabolic control is essential in development, as evident by the disorders caused by mutations in metabolic enzymes. The metabolic profile of cells is often cell‐type specific, changing as cells differentiate or during tumorigenesis. Recent evidence has shown that changes in metabolism are not merely a consequence of changes in cell state but that metabolites can serve to promote and/or inhibit these changes. Metabolites can link metabolic pathways with cell signaling pathways via several mechanisms, for example, by serving as substrates for protein post‐translational modifications, by affecting enzyme activity via allosteric mechanisms, or by altering epigenetic markers. Unraveling the complex interactions governing metabolism, gene expression, and protein activity that ultimately govern a cell's fate will require new tools and interactions across disciplines. On March 24 and 25, 2021, experts in cell metabolism, developmental biology, and human disease met virtually for the Keystone eSymposium, "Metabolic Decisions in Development and Disease." The discussions explored how metabolites impact cellular and developmental decisions in a diverse range of model systems used to investigate normal development, developmental disorders, dietary effects, and cancer‐mediated changes in metabolism. Abstract : Precise metabolic control is essential in development, as evident by the disorders caused by mutations in metabolic enzymes. Unraveling the complex interactions governing metabolism, gene expression, and protein activity that ultimately govern a cell's fate will require new tools and interactions across disciplines. On Demand content : https://keysym.us/EK27NYAS